Quantitative and Integrative Proteome Analysis of Peripheral Nerve Myelin Identifies Novel Myelin Proteins and Candidate Neuropathy Loci - Julia Patzig; Olaf Jahn; Stefan Tenzer; Sven P. Wichert; Patricia de Monasterio‐Schrader; Susanne Rosfa; Jörg Kuharev; Kuo Yan; Ingo Bormuth; Juliane Bremer; Adriano Aguzzi; Foteini Orfaniotou; et al. (2011)
Peripheral nerve myelin facilitates rapid impulse conduction and normal motor and sensory functions. Many aspects of myelin biogenesis, glia–axonal interactions, and nerve homeostasis are poorly understood at the molecular level. We therefore hypothesized that only a fraction of all relevant myelin proteins has been identified so far. Combining gel-based and gel-free proteomic approaches, we identified 545 proteins in purified mouse sciatic nerve myelin, including 36 previously known myelin constituents. By mass spectrometric quantification, the predominant P0, periaxin, and myelin basic protein constitute 21, 16, and 8% of the total myelin protein, respectively, suggesting that their relative abundance was previously misestimated due to technical limitations regarding protein separation and visualization. Focusing on tetraspan-transmembrane proteins, we validated novel myelin constituents using immuno-based methods. Bioinformatic comparison with mRNA-abundance profiles allowed the categorization in functional groups coregulated during myelin biogenesis and maturation. By differential myelin proteome analysis, we found that the abundance of septin 9, the protein affected in hereditary neuralgic amyotrophy, is strongly increased in a novel mouse model of demyelinating neuropathy caused by the loss of prion protein. Finally, the systematic comparison of our compendium with the positions of human disease loci allowed us to identify several candidate genes for hereditary demyelinating neuropathies. These results illustrate how the integration of unbiased proteome, transcriptome, and genome data can contribute to a molecular dissection of the biogenesis, cell biology, metabolism, and pathology of myelin.